KONFLIK DALAM PILKADA LANGSUNG : STUDI TENTANG PENYEBAB DAN DAMPAK KONFLIK - Nurhasim, Moch (Pusat Penelitian Politik, 2010)
The direct regional elections have been conducted smoothly andpeacefully since June 2005 to 2008 Howeversome ofthe elections have become conflictual The direct regional elections conflict describes two different interestsrom different actors which are the loser and the winner The winner are candidates who won the elections andhave been determined by the KPUD while the loser are those who were not determined by the KPUD as thewinner The loser actors oftenly questioned the voting results decided by the KPUD Many ways have been doneo raise this conftictual issues including through Law This study provides description of direct regional electionsconflict triggerfactors causalfactors behavior ofthe elite and mass in the conflict ways to solve the conflict byhe elite formal and non formal institutions The important thing of this study is description ofthe effects and theuture oflocal democracy in the post struggle ofpowerfollowed by political conflict and resistancy